Pengaruh Kinerja Keuangan, Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Industri Manufaktur Kriteria Syariah di Bursa Efek Indonesia: Studi Kasus Perusahaan Industri Manufaktur Periode 2021-2023 - Dyan Rachmawati; Sri Murwanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of financial performance, capital structure and company size on company value, with a case study of Manufacturing Industry Companies for the 2021-2023 Period. The methodology used in this study is a quantitative approach by utilizing secondary data in the form of annual financial statements of the company obtained from the official website of the Indonesia Stock Exchange (IDX) and other supporting sources. Sampling in this study used a non-probability technique (purposive sampling), so that 18 sharia manufacturing companies that met the research criteria were obtained. The analysis was performed using SPSS software. The results of the study show that financial performance (X1) has a significant influence on the Company's value, so H1 is accepted. On the other hand, the capital structure and size of the company have no significant effect on the value of the company, so H2 and H3 are rejected.